Global economic–biophysical assessment of midterm scenarios for agricultural markets—biofuel policies, dietary patterns, cropland expansion, and productivity growth - Ruth Delzeit; Gernot Klepper; Florian Zabel; Wolfram Mauser (Environmental Research Letters, 2018)
Land-use decisions are made at the local level. They are influenced both by local factors and by global drivers and trends. These will most likely change over time e.g. due to political shocks, market developments or climate change. Hence, their influence should be taken into account when analysing and projecting local land-use decisions. We provide a set of mid-term scenarios of global drivers (until 2030) for use in regional and local studies on agriculture and land-use. In a participatory process, four important drivers are identified by experts from globally distributed regional studies: biofuel policies, increase in preferences for meat and dairy products in Asia, cropland expansion into uncultivated areas, and changes in agricultural productivity growth. Their impact on possible future developments of global and regional agricultural markets are analysed with a modelling framework consisting of a global computable general equilibrium model and a crop growth model. The business as usual (BAU) scenario causes production and prices of crops to rise over time. It also leads to a conversion of pasture land to cropland. Under different scenarios, global price changes range between -42 and +4% in 2030 compared to the BAU. An abolishment of biofuel targets does not significantly improve food security while an increased agricultural productivity and cropland expansion have a stronger impact on changes in food production and prices.
Keywords: 330; global scenarios; global land use change; midterm scenarios; integrated modelling framework; computable general equilibrium model; dynamic crop growth model